CONCEPTUAL PROVISIONS OF BUSINESS PROCESS MANAGEMENT AT ENTERPRISES IN CONDITIONS OF DIGITALIZATION - LUPAK, Ruslan; NAKONECHNA, Nataliya (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article defines the key provisions of the formation and improvement of the business process management system at enterprises with a focus on adaptation to the dynamic conditions of digitalization. The further growth of the impact of digitalization on business activity and the need to make management decisions that allow for the establishment of business processes to respond to such trends as optimally as possible are emphasized. It has been proven that the correct choice of the business process management model is important in the activities of enterprises. The need for digitization and the use of information and communication technologies as a priority direction for improving the management of business processes at enterprises was noted. A number of advantages that the company receives from the implementation of investment-innovative and technical-technological activities and the importance of reorientation of management to the expansion of the spheres of business process management with the involvement of leading innovations and technologies have been identified. This orientation of enterprises to innovative development requires improvement of the management system, the vectors of which will be directed to the large-scale introduction of digital technologies and changes in the mechanisms of information transmission. The vectors and criteria for managing business processes at enterprises in the conditions of digitalization, which are associated with responding to risks and threats, increasing competitiveness, improving resource provision, and reformatting the organizational structure, are defined. It is emphasized that the implementation of digital technologies should be carried out on a large scale and this should be facilitated by the reorientation of the enterprise's management system to solve such a task.
Keywords: business processes; management; enterprises; digitalization; entrepreneurial activity; information technologies; innovations; innovative activity; strategies